CORPORATE GOVERNANCE AND CORRUPTION CONTROVERSIES IN SOUTHEAST ASIA - Mustika Ratu, Dewi (Faculty of Economics and Business University of Mataram, 2024)
The series of corporate corruption scandals has raised questions about the effectiveness of corporate governance. The focus of this investigation is on the interplay between ineffective corporate governance and corruption controversies among companies in Southeast Asia. Using archival methods, 515 firm-year observations were conducted in Indonesia, Malaysia, Thailand, and the Philippines between 2017 and 2021. As expected, research findings reveal a strong link between poor corporate governance and companies' involvement in corruption scandals. Furthermore, weak corporate governance diminishes the efficacy of anti-corruption initiatives in Southeast Asia. Consequently, a comprehensive understanding of the nexus between corporate governance and corruption scandals is of paramount significance for an equitable anti-corruption strategy. Urgent action is needed to enhance the monitoring of effective corporate governance implementation, which can contribute to the global fight against corruption.